Measurement of the Lambda b0 lifetime in Lambda b0-->J/psi Lambda 0 in pp collisions at square root s=1.96 TeV. - Abulencia, A; Adelman, J; Affolder, T; Akimoto, T; Albrow, MG; Ambrose, D; Amerio, S; Amidei, D; Anastassov, A; Anikeev, K; Annovi, A; Antos, J; et al. (2007)
We report a measurement of the Lambda b0 lifetime in the exclusive decay Lambda b0-->J/psi Lambda 0 in pp collisions at square root s=1.96 TeV using an integrated luminosity of 1.0 fb-1 of data collected by the CDF II detector at the Fermilab Tevatron. Using fully reconstructed decays, we measure tau(Lambda b0)=1.593(-0.078)(+0.083)(stat)+/-0.033(syst) ps. This is the single most precise measurement of tau(Lambda b0) and is 3.2sigma higher than the current world average.